تحسين توافرية وأداء النظام الموزع بإعادة انتشار مكونات النظام - حجازية, محمد; سليمان, علي (Latakia University Journal -Engineering Sciences Series, 2018)
استخدمت النظم الموزعة كثيراً في الآونة الأخيرة كبديل عن النظم المركزية نظراً لأدائها الأفضل عندما يزداد حجم النظام أو تزيد الحاجة إلى موارد المعالجة. رغم ذلك لازالت تعاني تلك النظم من مشاكل ضعف التوافرية عند حدوث تغيير في البنية التحتية التي تعمل فوقها مما أدى إلى ظهور مفهوم إعادة انتشار مكونات النظام الموزع. في هذا البحث تم تقديم طريقة لأخذ القرار بإعادة الانتشار الأفضل لبعض مكونات النظام الموزع عن طريق المراقبة الذاتية لحالة عقد النظام الموزع بالاستفادة من نظرية الأرتال، من ثم تقديم تقارير عن تلك الحالة إلى المكون المركزي، الذي يقوم حينئذٍ بأخذ قرار إعادة الانتشار إلى العقد المناسبة.Distributed Systems have been use too often recently as an alternative for central systems, due to their better performance when the size of the system or the need to the system resources becomes bigger. On the other hand, distributed systems are still fussing about the availability lack when a change of the infrastructure of the network take a place, which presents the approach of component redeployment in the distributed systems. In this research, we view a method for making decision about best component redeployment in a distributed system via self-monitoring for node status using the Queuing Theory, then handle reports to the central component, which make the choice about redeployment to the suitable node.